Ethnomathematics study of bamboo woven model in Yogyakarta based on Liki design matrix and its integration in mathematics learning - Sulistyawati, Eka; Radite, Ramadian (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2022)
This study aimed to analyze woven bamboo models in Yogyakarta based on Liki Design. Liki Design was sand painting design which was analyzed by Paul Gerdes. This study also described the integration of the results analysis in school mathematics. This research is a qualitative with an ethnomathematics approach. The woven bamboo model was analyzed based on the stages of data collection through interviews, documentation and collection of audiovisual materials, data separation, data analysis carried out by determining the main motif, coding the woven motifs into a matrix, analyzing using Liki Design, and conducting assessments between raters to prove the validity of the results. Based on the results by analyzed of 13 woven bamboo motifs obtained 6 corresponding matrix models. The integration of research results can be done in 2 ways, namely as context and content. As a context, the results of the analysis of woven motifs could be used to teach the context of matrix orders, number motifs, matrix operations, and geometric transformations. While integration in terms of content, research results can be used as content for mathematical exploration and technological literacy in the learning process.